2016
DOI: 10.1093/humupd/dmw027
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between androgens, FSH, anti-Müllerian hormone and estradiol during folliculogenesis in the human normal and polycystic ovary

Abstract: Within GCs, the balance between FSH and AMH effects is pivotal in the shift from androgen- to oestrogen-driven follicles. Our two triangles hypothesis, based on updated data from the literature, offers a pedagogic template for the understanding of folliculogenesis in the normal and polycystic ovary. It opens new avenues for the treatment of anovulation due to PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
243
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(264 citation statements)
references
References 152 publications
11
243
0
10
Order By: Relevance
“…The message provided by in vitro studies is that highly steroidogenic gonadotropins, i.e., FSH and hCG, mediate apoptotic stimuli in granulosa cells via cAMP/PKA-pathway (2, 3, 2931). In the ovarian setting of a multi-follicular maturation as in COS, stimulation is a potent signal for early tertiary follicle recruitment (34) and triggering steroidogenesis, results in estrogen over-production which, in turn, induces more pronounced multi-follicular survival and maturation (35) than that inducible by LH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The message provided by in vitro studies is that highly steroidogenic gonadotropins, i.e., FSH and hCG, mediate apoptotic stimuli in granulosa cells via cAMP/PKA-pathway (2, 3, 2931). In the ovarian setting of a multi-follicular maturation as in COS, stimulation is a potent signal for early tertiary follicle recruitment (34) and triggering steroidogenesis, results in estrogen over-production which, in turn, induces more pronounced multi-follicular survival and maturation (35) than that inducible by LH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…anovulation, hyperandrogenism and ultrasonographic features. 14 It is thought that androgens may play a key role in increasing the number of follicles 15 and induce follicular development. 16 Vendola et al 16 found a higher number of developing follicles with larger granulosa and theca cells in adult female Rhesus monkeys that received testosterone and dihydrotestosterone for treatment compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the estradiol level in follicular fluid from small antral follicles seems to be connected with AMH. It is likely that FSH induces a down regulation of AMH expression through rising follicle estradiol levels 24,25 There are at a minimum three biological characteristics that AMH displays which are clinically worthy and not in alignment with the conventional hormonal predictors of ovarian reserve. First, AMH is exhibited in granulosa cells of small growing follicles 8,9 Second, follicles that grow past the early antral follicle stage begin to lose their ability to express AMH, largely avoiding AMH measurements from bias that are linked to early follicular development, which is especially common in ovarian-aged women.…”
Section: Introductionmentioning
confidence: 99%